Vitamin D Supplementation for the Treatment of Acute Childhood Pneumonia: A Systematic Review - Das, Rashmi Ranjan (Hindawi Publishing Corporation, 2013)
Background. Studies have found an increased incidence of vitamin D deficiency in children with pneumonia; however, there is no conclusive data regarding the direct effect of vitamin D supplementation in acute pneumonia. Methods. A comprehensive search was performed of the major electronic databases till September 2013. Randomized controlled trials (RCTs) comparing treatment with vitamin D3 versus placebo in children ≤5 years old with pneumonia were included. Results. Out of 32 full text articles, 2 RCTs including 653 children were eligible for inclusion. One trial used a single 100,000 unit of oral vitamin D3 at the onset of pneumonia. There was no significant difference in the mean (±SD) number of days to recovery between the vitamin D3 and placebo arms (P = 0.17). Another trial used oral vitamin D3 (1000 IU for <1 year and 2000 IU for >1 year) for 5 days in children with severe pneumonia. Median duration of resolution of severe pneumonia was similar in the two groups (intervention, 72 hours; placebo, 64 hours). Duration of hospitalization and time to resolution of tachypnea, chest retractions, and inability to feed were also comparable between the two groups. Conclusions. Oral vitamin D supplementation does not help children under-five with acute pneumonia.